A knowledge-based measure of product complexity. (January 2018) - Zhang, Xiaoqi; Thomson, Vince
Highlights: A complexity measure is developed from the knowledge perspective. Technical complexity, integration complexity and product topology are captured. The measure is applied to improve the estimation of project effort and duration. The measure allows managers to identify knowledge mismatch. Abstract: This paper introduces a measure of product complexity from a knowledge perspective. A product is considered to be the result of integrating functions; so, the measure considers the complexity of individual functions as well as integration tasks. Disciplinary knowledge required in product design is classified and quantified. The complexity of each individual function is a measure of the intensity of knowledge requirements. The complexity of integrating two functions is a measure of the product of knowledge difference and interdependency. The application of the new method for the estimation of design effort and project duration is illustrated with an example of a hydroelectric generator.